Lund Virtual Medical Journal Makes Self-Archiving Attractive and Easy for Authors - Hultman Özek, Yvonne (D-Lib Magazine, 2005)
This article highlights the importance of communication and collaboration with units outside the library to make self-archiving attractive to authors. The monthly electronic publication, Lund Virtual Medical Journal (LVMJ), published by the Department of Strategic Communication of the Faculty of Medicine at Lund University, started as a response to the need to increase the visibility of ongoing research by the Lund University faculty, and with the aim of showing all published faculty-authored articles. At the time the journal was launched, Lund University Libraries Head Office had set up their institutional repository for the university, LU:research. This article describes features of LVMJ and the synergistic relationship between LU:research and LVMJ. It also discusses some of the challenges in producing LVMJ and future plans for the journal.
Keywords: Information science; Open Access; institutional repositories; self-archiving